Examining the Role of E-Satisfaction and E-Trust Toward Repurchase Intention on Online Marketplace Mediated by Electronic Word of Mouth - Agung Kresnamurti Rivai Prabumenang; Shandy Aditya; Shalfa Shabrina Nurul An nisa (LPPM Universitas Negeri Jakarta, 2023)
This study aims to determine the effect of e-satisfaction on electronic word of mouth, the effect of e-trust on electronic word of mouth, the effect of electronic word of mouth on repurchase intention, the effect of e-satisfaction on repurchase intention, the effect of e-trust on repurchase intention, the effect of e-satisfaction on repurchase intention through electronic word of mouth, the effect of e-trust on repurchase intention through electronic word of mouth, on Tokopedia online marketplace customers. The data collection in this study was by distributing questionnaires to 200 Tokopedia online marketplace customers. In analyzing the research data, the Structural Equation Model (SEM) approach was used with the Lisrel application version 8.8. The results of this study are there is a positive and significant effect on e-satisfaction on electronic word of mouth, there is a positive and significant influence on e-trust on electronic word of mouth, there is a positive and significant influence on electronic word of mouth on repurchase intention, there is a positive influence and significant on e-satisfaction on repurchase intention, there is a positive and significant effect on e-trust on repurchase intention, there is a positive and significant effect on e-satisfaction on repurchase intention through electronic word of mouth, there is a positive and significant effect on e-trust on repurchase intentions through electronic word of mouth, in the online marketplace Tokopedia.